Perancangan Aplikasi Kunjungan Kehamilan Berbasis Android - Meyti Eka Apriyani; Abdul Qodir (JURNAL INTEGRASI, 2014)
The problem that often leads to death of a baby is a lack of information about pregnancy and lack of awareness of the health of pregnant women to perform control or pregnancy visit to the doctor or midwife. The system is designed to make it easier for pregnant women to obtain information and exercise control over the visit of pregnancy. This application can display the schedule of visits the patient and can display pregnancy patient health information. The application also has a queue register online menu, display the number of patients queuing and queue displays running.